Legal Aspects of the High Court's Authority in Freezing the Minutes of the Advocacy Oath - Pandri Zulfikar; Moro Asih, Mohammad (Universitas Pahlawan Tuanku Tambusai, 2025)
The authority of the High Court in freezing the Advocate Oath Minutes (BAS) is a complex legal aspect and has implications for the independence of the advocate profession and the judicial system in Indonesia. This study aims to analyze the legal basis, authority, and limitations of the High Court in freezing the BAS of Advocates, as well as its impact on the rights of advocates and the national legal system. The research method used is a normative juridical approach by examining relevant laws and regulations, court decisions, and relevant legal doctrines. The results of the study show that the High Court's authority in freezing BAS Advocates still faces ambiguity in regulations, so it has the potential to cause legal uncertainty. In addition, the freezing of BAS can have an impact on limited access to justice and freedom of the advocate profession in carrying out their duties. Therefore, clearer and more consistent regulations are needed to avoid potential abuse of authority and ensure the principle of due process of law in the Indonesian legal system.